Vers la fin d’un symbole du pouvoir local ? Le cumul des mandats - Messaoud Saoudi (Cahiers Jean Moulin)
Being interested in multiple office-holding as “holy secularism" of local power means wondering about an old political practice introduced by the Revolution of 1789 and anchored in our institutions since the Third Republic. This regime, established by the constitutional laws of 1875, has the merit for the first time to connect by legalizing him, multiple office-holding and the accumulation of allowances. We shall limit ourselves to the French local political power through one of its major symbols, the multiple office-holding of the representatives of regions with a measure of autonomy and\or EPCI with their own tax system. Local power, as any political power, infringes on the domain of the sacred and feeds on religious references (faiths, myths, rites and symbols). The analysis of the normative reach of the organic and ordinary laws of 2014 as well as their symbolic impact seems to show that the legislator did not fundamentally question the principle of multiple office-holding as a strong symbol of local power.